Development of Electric Cube Assistive Technology to Facilitate Physical Fitness Trainings of Children With Special Needs - Darmawan, Arief; Fathur Rohman, Moh.; Sugiarto, Tatok; Setia Lengkana, Anggi; Tra Giang, Nguyen; Rizki Fakhruddin, Anhar (KnE Social Sciences, 2022)
Assistive technology has opened many doors of education for special needs students. Assistive technology can be an equalizer for individuals with special needs to be able to participate in the school and community environment. This study aimed to research and develop assistive technology that can facilitate special needs children to be able to do physical activities like physical fitness exercises. The final product of this study is a smart cube equipped with a timer and a special fitness training program that is integrated into the smartphone. The research method used in this study was research and development adopted from Borg and Gall, divided into three stages. The design stage, the development stage, and the implementation stage. The research subjects consisted of experts in adaptive physical education, physical activity instructors for students with disabilities, and students with disabilities. Data was collected using the test method (physical fitness movement literacy) and non-test methods (survey, test, observation, interview and documentation). The results of the small group and large group try out stated that the product can be implemented well, and by looking at the results of the research, it can be concluded that the product is suitable to use by children with special needs, especially children with mild mental disabilities. Keywords: Assistive device, Electric cube, Physical fitness, Special needs children